Mr. Monk goes to Germany - Goldberg, Lee, 1962- (Monk series (New York, N.Y.), 2008)
Adrian Monk has actually been doing well lately. He's solving murders as fast as they come, and he's been noticeably less compulsive. Monk knows he owes it all to his therapist, Dr. Kroger. So when Kroger attends a conference in Germany, Monk hits the skids, reverting to his OCD habits full-time. Desperate, Monk follows his shrink to Germany. And that's when he sees the man across a crowded town square. A man with six fingers. Monk knows it could be the man responsible for his wife's death.